Formulation and Evaluation of Floating Matrix Tablets of an Antipsychotic Drug - Jayashree, Dasari Durga (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2023)
Dosage forms that can be retained in the stomach are called gastroretentive drug delivery systems (GRDDSs). GRDDS can improve controlled delivery of drugs with an absorption window by continuously releasing the drug for a prolonged period before it reaches its absorption site, thus ensuring optimal bioavailability. Prolonged gastric retention improves bioavailability, reduces drug waste, and improves solubility of drugs that are less soluble in a high pH environment. It is also suitable for local drug delivery to the stomach and proximal small intestines. Gastroretention helps to provide better availability of new products with suitable therapeutic activity and substantial benefits for patients. This mode of administration would best achieve the known pharmacokinetic and pharmacodynamics advantages of CR-DFs of these drugs. In the present study, Ziprasidone was selected as model drug in the design as GFDDS using various lipoidal/fatty polymers. Ziprasidone complies with all the requirements that are suitable for a drug candidate to be formulated as GFDDS, as it has specific site of absorption in upper part of GIT. Since the half-life of Ziprasidone is 2 h, the optimized polymer with best floating and retarding ability, that is, Gelucire 43/01 is subjected to aging studies to assess the effect of ageing by differential scanning calorimetry. Hence, it is evident that the non-effervescent gastro retentive floating multi-unit formulations of Ziprasidone is feasible and may be manufactured with reproducible characteristics with the aid of Gelucire 43/01 as polymer.